Experimental investigation of the interference of a body on a low aspect ratio wing of rectangular planform at a Mach number of 2 - Busing, J. R.; Marson, G. B.; Lilley, G. M. (College of Aeronautics, 1955)
Results are given of pressure measurements on awing of gross aspect ratio approximately 2/3 mounted on a cylindrical body with an ogival nose, made at a Mach number of 2.00 in the 9in, x 9in, supersonic -wind tunnel at the College of Aeronautics. The wing section was a single wedge having a 6° total nose angle. The ranges of body incidence and roll in these tests were from 0° to 30°, and 0°, 30°, 600 and 90° respectively. The normal force, lift, drag and side force coefficients, and rolling and pitching moments were obtained from the pressure measurements.